2008
DOI: 10.1007/s11011-008-9087-4
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan administration induces oxidative stress in brain cortex of rats

Abstract: Despite the significant brain abnormalities, the neurotoxic mechanisms of brain injury in hypertryptophanemia are virtually unknown. In this work, we determined the thiobarbituric acid-reactive substances, 2',7'-dihydrodichlorofluorescein oxidation, reduced glutathione and the activities of catalase, superoxide dismutase and glutathione peroxidase in cerebral cortex from rats loaded with L-tryptophan. High L-tryptophan concentrations, similar to those found in hypertryptophanemic patients were induced by three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…In addition, several studies have showed that tryptophan loading could induce oxidative stress in brain cortex of rats, and tryptophan metabolism may contribute to brain damage following stroke. [ 31 32 ] In the present study, we determined that several tryptophan metabolites were decreased during the early stage after ASCP that may alleviate brain oxidative damage. Besides, KYN has been known to play an important role in the process of neuronal damage and neurodegenerative disorders, and it could promote oxidative stress following a stroke.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, several studies have showed that tryptophan loading could induce oxidative stress in brain cortex of rats, and tryptophan metabolism may contribute to brain damage following stroke. [ 31 32 ] In the present study, we determined that several tryptophan metabolites were decreased during the early stage after ASCP that may alleviate brain oxidative damage. Besides, KYN has been known to play an important role in the process of neuronal damage and neurodegenerative disorders, and it could promote oxidative stress following a stroke.…”
Section: Discussionmentioning
confidence: 94%
“…TRP is widely available on the market as a supplement for both animals and humans. However, there have been concerns that excess administration of TRP may cause oxidative stress in the cerebral cortex (91), as well as other adverse effects, including ataxia, tremors, diaphoresis, blurred vision, dry mouth, muscle stiffness, palpitations, urticaria, and the "eosinophilia-myalgia syndrome" (EMS) (92)(93)(94)(95)(96)(97). However, some of these side effects might have been caused by contaminated substance(s) in the former TRP preparations, but not TRP itself.…”
Section: Safety Of Oral Trp and Its Metabolitesmentioning
confidence: 99%
“…Furthermore, oxidative stress due to Trp loading can also be prevented by the pretreatment with antioxidants. Thus the hypothesis of Trp-induced oxidative stress in brain cortex has been elucidated by giving taurine or alpha-tocopherol plus ascorbic acid (Feksa et al 2008 ). Nonspecifi c NOS inhibitors decrease the homocysteine-induced lipid peroxidation than does the selective neuronal NOS inhibitor.…”
Section: Hypertryptophanemiamentioning
confidence: 99%